Censura e liberdade de expressão: manifestações artísticas e o estado democrático de direito - Prodorutti Alves, Ana Carolina (2023)
This research studies freedom of expression in Brazil and censorship, focusing on artistic manifestations that have occurred in recent years. One of the cores of the Democratic State of Law is freedom of expression, which allows everyone to have the right to express their opinions freely through any form of artistic expression. It is for this reason that the social and legal repercussions of the Queermuseu exhibition and other exhibitions are still important and deserve the attention of the legal world, especially the understanding of the limits to freedom of artistic expression in Brazilian law - a problem that is being attacked. For this, fundamental rights and their limits are studied, as well as the freedom of artistic expression as a manifestation of thought, which allows the understanding of the Queermuseum exhibition and other exhibitions. The hypothetical-deductive method is used, to confirm, in conclusion, the hypothesis that the State must guarantee, through the action of all powers at all levels of the Federation, the freedom of artistic expression, which can only be mitigated by collision with other fundamental rights, which did not occur in the analyzed exposures.